Enhancing Interest and Achievement: Development of Smartbox Learning Media in Pancasila Education - Chintya, Chintya Asti Halizha; Fathurrahman, Mohammad (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2025)
This study aimed to develop Smartbox learning media to enhance student interest and learning achievement in Pancasila Education for third-grade elementary students. The research employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The study was conducted at SD Negeri Salamsari, involving 30 third-grade students as participants. Data were collected through expert validation forms, student questionnaires on learning interest, pre-test and post-test assessments, classroom observations, and teacher interviews. The media received high validity scores from experts: 93.3% from media experts and 97.5% from material experts. After implementation, student motivation and participation increased significantly, and the average academic scores improved from 58 in the pre-test to 82 in the post-test. These results suggest that the Smartbox is an effective learning tool for transforming abstract Pancasila concepts into engaging, concrete learning experiences that support both student motivation and academic achievement.